The investigation of the kinetics of initiated chemilumenescence of the blood serum - Gotra, Z.Yu; I.Ya. Oliynyk, I.Ya. (Biophysical Bulletin, 2005)
The present work is dedicated to the investigation of kinetic properties of the initiated chemiluminescence under such illnesses as cancer tuberculosis and sarcoidosis. In particular, we perform the complex analysis of the maximum flash of intensity and integral lights under different illnesses. It is established the decrease of the intensity of the maximal flash comparing with normal value under cancer of III study and increase under the IV study. The integral lights are less than normal value. Under tuberculosis and sarcoidosis, the increase of these properties takes place. The kinetic analysis follows the necessity of () of the curves in coordinates. It has been confirmed in the experiment. The tangent of bias angle is different under all illnesses. In particular, it is established its considerable increase under cancer. The data obtained are explained by differences in the number of the reaction centers.